Comparaciones radiográfica y clínica del diagnóstico de las reabsorcione radiculares en dientes deciduos (2001)
ABSTRACT: This study was designed to clinically and radiographically compare the degree and type of root resorption in the deciduos dentition, and to define the limitations of periapical radiographs to diagnose such resorption. 12 patients whose ages ranged from 5-13 years and who were attending the clinics of the College of Dentistry of the University of Antioquia were selected, among them, a total of 16 teeth were collected (9 monoradicular, -7 multiradicular). The results indicated: 1) concordance is low not only for the degree but also for the type of resorption in multi-rooted teeth. 2) the monoradicular teeth, concordance is high for the degree, but it is low for the type of root resorption. 3) concordance, as it refers to degree and type of resorption improved when the resorption is advanced, both for the monoradicular as well as for the multiradicular teeth.